A Critical Review of the Goal of Natural ising Epistemology - Oladipo, Temidayo David (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
The focus in this article is on the examination of the goal of naturahs d epistemology which seeks to replace the philosophical inquiry into epistemology" ith the methodology of science. It is argued in the paper that the proposal for naturalised epi temology undermines the importance of the methodology of conducting philosophi al inquiry, and hence the philosophical treatment of issues in epistemology, as well as the Importance of philosophical inquiry into science. It is concluded that although other means of analysing knowledge may emerge, yet. epistemology will have to continue to evaluate human knowledge philosophically because the philosophical quest for knowledge is a reminder that we can be better than we are, that there are lofty heights of ideals yet to be attained, and search for which we must not relent. Our position is that this philosophical quest is what is responsible for keeping the insatiable human spirit searching, and researching for the perfection, which according to Plato, resides in the world of forms. At the heart of this search is the conviction that certainty, absolute truth. is radically different from scientific discovery about it.